Sikhism and Christianity - Cole, W.O. author. aut Link
XII, 221 p.
Keywords: This volume will provide a thorough comparison of the rituals, beliefs and history of Sikhism and Christianity. Chapters will focus on God, revelation, the scriptures, worship, ethics and the history of these two religions, and will highlight both differences and similarities.